Structure and expression of STK, a src-related gene in the simple metazoan Hydra attenuata. - Bosch, T C (1989)
Both cDNA clones and a genomic DNA clone encoding a 509-amino-acid protein that is 64% similar to chicken pp60c-src were isolated from the simple metazoan Hydra attenuata. We have designated this gene STK, for src-type kinase. Features of the amino acid sequence of the protein encoded by the STK gene suggest that it is likely to be myristoylated and regulated by phosphorylation in a manner similar to that found for pp60c-src. The genomic sequence encoding the protein was found to be interrupted by at least two introns, one of which was located in a position identical to that of one of the introns in the chicken src gene. The STK gene was expressed during early development of H. attenuata and at high levels in the epithelial cells of adult polyps. Probing of Hydra proteins with an antibody to phosphotyrosine indicated that the major phosphotyrosine-containing protein in H. attenuata may be the STK protein itself. H. attenuata is the simplest organism from which a protein-tyrosine kinase gene has been isolated. The presence of such a gene in the evolutionarily ancient phylum Cnidaria suggests that protein-tyrosine kinase genes arose concomitantly with or shortly after the appearance of multicellular organisms.